Enhancing emollient properties of natural and structured virgin coconut oil creams on skin conditions using non-invasive skin biophysical methods - Salizatul Ilyana Ibrahim,; Juan Matmin,; Nuriana Munirah Hairul,; Abu Bakar Abdul Majeed, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to evaluate the emollient properties of natural-based oil creams on skin conditions. The focus is primarily on natural virgin coconut oil (VCO) and structured VCO (SVCO) which contain medium-chain triglycerides (MCTs) that have been reported to have a permeation enhancement effect on the lipophilic active ingredient. SVCO, which contains a higher amount of MCTs than VCO, was produced by lipase-catalyzed acidolysis of caprylic/octanoic acid (eight-carbon chain) and VCO. The emollient cream was prepared using the oil in water (o/w) formulation cream and it consisted of 30% (w/w) of oils, emulsifying wax, and deionized water. While in the oil phase, 5% (w/w) α-tocopherol, the model lipophilic active ingredient was added to the cream. Significant effects (p<0.05) were statistically produced in the skin moisture content, transepidermal water loss (TEWL), and skin elasticity values for all formulations as compared to the skin at T0 (before application) after the short- and long-term study periods. The skin smoothness (SEsm) and skin roughness (SEr) values, which are indicators of the skin condition, also showed significant improvement. The results indicated that VCO and SVCO creams exerted an emollient effect when applied topically and also acted as skin permeation enhancers in the formulation.